Animal behaviour - Tinbergen, Niko. (New York : Time life books, 1965)
This essential reference work presents the study of animal learning and cognition especially in a comparative sense with humans. It brings together seminal papers from the last century in this major area of research in experimental psychology and behavioral biology
Includes bibliography and index.
Keywords: Animal behavior; Animals -- Habits and behavior; Diergedrag